2001
DOI: 10.1016/s1074-7613(01)00226-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of IFN-γ Signaling by an Epstein-Barr Virus Immediate-Early Protein

Abstract: Viruses have evolved elaborate mechanisms to target many aspects of the host's immune response. The cytokine IFN-gamma plays a central role in resistance of the host to infection via direct antiviral effects as well as modulation of the immune response. In this study, we demonstrate that the Epstein-Barr virus (EBV) immediate-early protein, BZLF1, inhibits the IFN-gamma signaling pathway. BZLF1 decreases the ability of IFN-gamma to activate a variety of important downstream target genes, such as IRF-1, p48, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
117
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(121 citation statements)
references
References 69 publications
4
117
0
Order By: Relevance
“…87 IFNγ plays an essential role in the control of many different infectious diseases. It stimulates intracellular and intercellular network and mediates activation of cytotoxic effector function of innate and adaptive immunity cells.…”
Section: Regulation Of Cellular Gene Expression By Ztamentioning
confidence: 99%
“…87 IFNγ plays an essential role in the control of many different infectious diseases. It stimulates intracellular and intercellular network and mediates activation of cytotoxic effector function of innate and adaptive immunity cells.…”
Section: Regulation Of Cellular Gene Expression By Ztamentioning
confidence: 99%
“…Of special note is the identification of a series of cell cycle regulatory genes such as p21 CIP1 , p53, CDC25A and E2F1. In addition, it has recently been shown that the expression of the IFN-c receptor is regulated by Zta (Morrison et al, 2001). Expression of the IFN-c receptor gene is downregulated at both the RNA and protein levels following introduction of an adenovirus vector expressing Zta.…”
Section: Ability Of Zta and K-bzip To Regulate The Cell Cyclementioning
confidence: 99%
“…Expression of the IFN-c receptor gene is downregulated at both the RNA and protein levels following introduction of an adenovirus vector expressing Zta. Furthermore, this translates into an ability of Zta to functionally disrupt the IFN-c signal transduction pathway (Morrison et al, 2001), which has implications for the ability of EBV to survive during primary infection and lytic cycle replication in vivo.…”
Section: Ability Of Zta and K-bzip To Regulate The Cell Cyclementioning
confidence: 99%
“…In a number of tumors and viral oncogene-expressing cell lines, down-regulation of the physical levels or inactivation of the components of ISGF3 serves as a mechanism for evading the action of IFNs (9,10). ISGF3 is targeted by adenovirus (10), human papilloma (11,12), EpsteinBarr (13), and hepatitis C viruses 2 for evading the antiviral action of IFNs.…”
mentioning
confidence: 99%